THE ROLE OF CLINICAL PARAMETERS IN THE PATIENT EXAMINATION PROGRAM AS AN OPTIMIZATION MEANS FOR COMPLEX DIAGNOSIS AND PROGNOSIS OF TEMPOROMANDIBULAR JOINT DISEASES - Ozhogan, Z. R.; Krokhmal, A. V. (Art of Medicine, 2023)
Aim: to optimize the diagnosis and the choice of treatment tactics for temporomandibular joint (TMJ) pathology by evaluating the features of its clinical manifestations. Materials and methods: in a clinical retrospective randomized cohort dynamic study as part of a comprehensive examination, an assessment of clinical, anamnestic, and physical symptoms was conducted in 325 patients aged 18 to 76 years with TMJ diseases and accompanying pathology, in particular, periodontal diseases, pathological attrition, dentition defects. Data analysis was conducted using classical methods, considering the types of data and their distribution at a critical level of p 0.05. Results and discussion. Anamnestic and physical indicators show stable trends in patients with TMJ changes and comorbid conditions already long before development to clinically significant dental pathology (by descending informativeness): pain in the TMJ area, pain during wide opening of the mouth, noises in the TMJ area, the desire to find the most comfortable position of the jaws when closing the teeth, disturbances in chewing and diction, asymmetry of the movements of the lower jaw in the horizontal plane, treatment with the use of corrective history of mouth gags, teeth grinding or clenching, chronic pain in the temporal region, pronounced sensitivity in the area of the teeth, cramps in the head or neck and throat, orthodontic treatment or selective grinding of teeth in the anamnesis, history of serious accidents or intubation, disorders of the masticatory muscles, previous dental treatment, pathology of hard tissues of teeth, misalignment of the centers of the tooth rows, mismatch of centers behind bridles, failure of the patient to perceive the seriousness of the condition, violation of posture, absence of the need for treatment in the patient's perception, etc. A method (algorithm) of assessing the probability of progression of TMJ diseases was developed based on the data of the study of the frequency of individual factors and the prognostic value of each of the criteria. For each clinical indicator, its presence or absence is determined, and the corresponding values of informativeness are added. When the threshold sum of coefficients is reached using the scale, a risk group of progression of TMJ disorders is determined: if the sum is equal to or lower than -19.8, the risk is high; if the sum is greater than -19.8 and less than 19.8, the risk is uncertain; if the sum is equal to or higher than 19.8, the risk is low. Following conclusions were made: both anamnestic and physical clinical manifestations (bruxism, myofascial pain, palpation data, malocclusion, pathological wear of teeth, periodontopathy, etc.) are important components in the early diagnosis of TMJ pathology and the selection of optimal correction tactics. Taking into account the clinical indicators in general semiotics allows to optimize the diagnosis and the choice of medical care tactics for persons with TMJ problems already at the pre-clinical stage; clinical parameters should be taken into account in the development of a patient examination program as a means of optimizing complex diagnosis and prognosis of TMJ diseases using axiography. Prospects for further research — assessment of the prognostic ability of clinical indicators in patients with diseases of the TMJ with further development of a prognostic program for the development and course of this pathology considering the data of a complex of condylographic and electromyographic indicators.